Water protozoa and diseases of the population of Ologa and Congo Mirador, Maracaibo Lake, Venezuela. (Revista Venezolana de Salud Pública, 2019)
The poor diet and absence of minimal sanitary elements, in the populations of Ologá and Congo Mirador, make their inhabitants susceptible to suffer from a diversity of mainly infectious and nutritional diseases, which alert the need to address these problems in a constant and sustained manner.
Keywords: water; health; protozoa